1993
DOI: 10.1007/bf01607150
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-immunophenotypic diversity of Castleman's disease, hyaline-vascular type: With emphasis on a stroma-rich variant and a new pathogenetic hypothesis

Abstract: A histologic review of 102 cases of Castleman's disease of the hyaline-vascular type, with a detailed paraffin immunophenotypic study of 23 of them, was undertaken to evaluate the morphologic variability of this disorder and its immuno/cyto-architectural characteristics. All cases had features in common including: abnormal follicles, with increased vascularity, poorly formed germinal centers and predominance of the mantle zone; lack of sinuses; and hypervascular interfollicular tissue containing large numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
0
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 34 publications
4
59
0
7
Order By: Relevance
“…The diagnosis was reviewed by three hematopathologists and the hyaline vascular Castleman disease cases were further subclassified as classical, lymphoid, 8 and stromal-rich variant. 9,11 The classical cases of hyaline vascular Castleman disease showed regressed and confluent follicles with radially penetrating sclerotic arterioles ('lollipop lesion'), hyaline deposits in germinal centers, concentric layering of mantle zone lymphocytes ('onion skin appearance'), inapparent sinuses, and interfollicular vascular hyperplasia (Figures 1a and b). The lymphoid variant was characterized by mantle zone expansion around the atrophic, inconspicuous germinal center that may mimic follicular lymphoma or mantle cell lymphoma (Figure 1c).…”
Section: Female Cases Of Hyaline Vascular Castleman Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis was reviewed by three hematopathologists and the hyaline vascular Castleman disease cases were further subclassified as classical, lymphoid, 8 and stromal-rich variant. 9,11 The classical cases of hyaline vascular Castleman disease showed regressed and confluent follicles with radially penetrating sclerotic arterioles ('lollipop lesion'), hyaline deposits in germinal centers, concentric layering of mantle zone lymphocytes ('onion skin appearance'), inapparent sinuses, and interfollicular vascular hyperplasia (Figures 1a and b). The lymphoid variant was characterized by mantle zone expansion around the atrophic, inconspicuous germinal center that may mimic follicular lymphoma or mantle cell lymphoma (Figure 1c).…”
Section: Female Cases Of Hyaline Vascular Castleman Diseasementioning
confidence: 99%
“…The stromal-rich variant was defined as a prominent interfollicular zone occupying 50% or more of the nodal area. 11 The interfollicular zones had increased stromal cells and blood vessels and were associated with residual lymphoid follicles (Figure 1d). The frequent components of stromal cells were actinpositive 'myoid' cells and follicular dendritic cells.…”
Section: Female Cases Of Hyaline Vascular Castleman Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The localized type of the disease presents with a slow growing, progressive and painless lymph node enlargement and is situated cervical (42%), mediastinal (31%), abdominal (18%) and retroperitoneal (5%). 7) Other authors reported that the majority of CD is detected mediastinal (46%-70%), only 3%-39% intraabdominal and 10%-15% is seen in the periphery. 8) These differences are due to different diagnostic algorithms and to the low incidence of the disease.…”
Section: Discussionmentioning
confidence: 93%
“…The cause of CD is unknown; it is discussed that the localized type is started by an antigen stimulus of an abnormal plasmacytoid monocyte population in a lymph node. 7) The multicentric form is believed to be induced by chronic infection. The treatment of choice for the localized form of CD is complete surgical resection including systematic lymph node dissection, resulting in cure in all reported cases.…”
Section: Discussionmentioning
confidence: 99%